Pengaruh Kualitas Pelayanan dan Harga Terhadap Minat Berkunjung Kembali di Café Damar Shaker Padang Baru - Juliani Juliani; Waryono Waryono (Jurnal bintang manajemen, 2025)
This research aims to assess how service quality and pricing affect the likelihood of returning to Café Damar Shaker Padang Baru. The study uses a quantitative approach with a causal associative model, employing a survey methodology. The research population comprises customers of Café Damar Shaker Padang Baru, with a sample size of 130 respondents. A non-probability sampling method, specifically purposive sampling, was used. The research instruments were tested for validity and reliability. Analysis included tests for normality, heteroscedasticity, and multicollinearity. Hypothesis testing was conducted using multiple linear regression and the coefficient of determination. Findings reveal that service quality, pricing, and the intention to revisit are all rated highly, with average scores of 4.64, 4.67, and 4.71 respectively. The multiple linear regression analysis produced an F value of 64.723 with a significance level of 0.000 (p < 0.05), confirming the validity of the regression model. The Adjusted R Square value of 0.497 indicates that service quality and pricing account for 49.7% of the variation in the intention to revisit Café Damar Shaker Padang Baru, while the remaining 50.3% is influenced by other factors not examined in this study. Consequently, the alternative hypothesis (Ha) is supported.